Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Tim Pada PT.Sompo Insurance - Nabila Rahmadini (Global Leadership Organizational Research in Management, 2025)
PT. Sompo Insurance is one of the many insurance companies in Indonesia, and has many branches located in many countries. At PT. Sompo Insurance Indonesia writers will examine the relationship between the influence of leadership style and communication that will affect the performance of the team.. The sample in the study was 38 respondents using saturated sampling techniques, all populations in this study were used as research samples. The data collection technique uses a questionnaire method with a Likert scale. Based on the results of this study, the Leadership Style variable (X1) has a positive and significant influence on Team Performance (Y) obtained from the calculation of the calculation of the ttable > (4.217 > 1.690) with a significance level of 0.001 < 0.05. The Communication Variable (X2) has a positive and significant influence on Team Performance (Y). This is shown from the results of the calculation of the tcount > ttable (5.176 > 1.690 ) with a significant level of 0.001<0.05. Simultaneously, the variables of Work Environment (X1) and the variables of Employee Performance (X2) have a positive and significant influence on Team Performance (Y). This was obtained from the results of the calculation of Fcount of 171.585 with a significant level of 0.001 < 0.05 and Fcal > Ftabel (171.585 > 3.27). The results of the determination coefficient (R2) analysis obtained R Square of 0.907 or 90.7% were influenced by the Leadership Style variable (X1) and the Communication variable (X2) while the remaining 9.3% was influenced by other independent variables that were not studied in this study.